Centenarians in India: the present scenario - Bhattacharyya, Kallol Kumar (International Journal Of Community Medicine And Public Health, 2017)
India, officially the Republic of India is a country in South Asia. It is the seventh-largest country by area, the second-most populous country (with over 1.2 billion people), and the most populous democracy in the world. A country of myriad subcultures which constitutes a unique phenomenon of ‘unity in diversity’. India is the home of people of various ethnicity, religion, culture and languages. It has its own primitive cultures. Later, in different times this country was attacked by Greek, Shak, Hun, Pathan, Mughal, British, Dutch, French etc. So there is a diverse collection of culture and ethnicity, rather a conglomeration of these. The number of 100-year-olds in India has steadily increased over the last few decades. Keeping the above background in mind, the present scenario—the prospects, expectations and problems faced by a large number of centenarians scattered in different regions of this country, has discussed in this review.